2008
DOI: 10.1007/s10549-008-9897-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signatures of neoadjuvant endocrine therapy for breast cancer: characteristics of response or intrinsic resistance

Abstract: Approximately 30% of patients with estrogen receptor (ER) positive breast cancers exhibit de novo or intrinsic resistance to endocrine therapies. The purpose of this study was to define genes that distinguish ER+ resistant from ER+ responsive tumors, prior to the start of hormone therapies. Previously untreated post-menopausal patients with ER+ breast cancers were treated for 4 months in a neoadjuvant setting with the aromatase inhibitor exemestane alone, or in combination with the antiestrogen tamoxifen. Matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 58 publications
1
56
0
Order By: Relevance
“…Changes in gene expression profiles in breast cancer tumours during endocrine treatment have been reported before (Kristensen et al, 2005;Mackay et al, 2007;Miller et al, 2007Miller et al, , 2009Harvell et al, 2008). To our knowledge this is the first study evaluating expression of nuclear receptor co-regulators in breast cancer patients during oestrogen deprivation.…”
Section: Discussionmentioning
confidence: 58%
“…Changes in gene expression profiles in breast cancer tumours during endocrine treatment have been reported before (Kristensen et al, 2005;Mackay et al, 2007;Miller et al, 2007Miller et al, , 2009Harvell et al, 2008). To our knowledge this is the first study evaluating expression of nuclear receptor co-regulators in breast cancer patients during oestrogen deprivation.…”
Section: Discussionmentioning
confidence: 58%
“…The study was fueled by previous observations that in ER-positive breast cancer responding to endocrine treatment, AR downregulation at the protein and mRNA level is observed, whereas no such effect is seen in nonresponsive tumors (56,57). In a cohort of 192 patients with earlystage ER-positive breast cancer receiving adjuvant tamoxifen treatment and another one of a randomized phase II trial assessing exemestane with or without tamoxifen, high AR:ER ratio was found to predict resistance to endocrine therapy in a statistically significant manner.…”
Section: Discussionmentioning
confidence: 99%
“…AIs block the conversion of androgen to estrogen, thus increasing free testosterone and DHEA-S [70]. Previous studies have shown that patients with ER positive tumors that are responders to neoadjuvant AI therapy, display decreased AR mRNA and nuclear protein, while non-responders continue to have elevated AR expression [71, 72]. Our data are in accordance with previous reports that AR overexpression in breast cancer cell lines leads to tamoxifen and AI resistance [65, 73].…”
Section: Discussionmentioning
confidence: 99%